2020
DOI: 10.1002/cssc.201903025
|View full text |Cite
|
Sign up to set email alerts
|

3 D NiO Nanowall Hole‐Transporting Layer for the Passivation of Interfacial Contact in Inverted Perovskite Solar Cells

Abstract: Nickel oxide (NiO) materials with excellent stability and favorable energy bands are desirable candidates for hole‐selective contact (HSC) of inverted perovskite solar cell (PSC). However, studies that focus on addressing interfacial issues, which are induced by the poor NiO/perovskite contact or other defects, are scarce. In this study, a facile one‐step hydrothermal strategy is demonstrated for the development of a 3 D NiO nanowall (NW) film as a promising HSC. The new NiO NWs HSC exhibits a robust and homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…As shown in Figure 4d, the PL quenching of the perovskite film grown on MEA‐modified m‐TiO 2 is much more efficient than that of the unmodified m‐TiO 2 , suggesting enhanced electron extraction and reduced charge recombination. [ 27 ] In addition, TRPL spectra collected at the emission peak (760 nm) of the perovskite on bare TiO 2 and MEA‐passivated TiO 2 are shown in Figure 4e. The TRPL spectra showed a biexponential decay, in which the fast decay lifetime ( τ 1 ) can be ascribed to the trap‐assisted nonradiative recombination and the longer decay lifetime ( τ 2 ) can be attributed to the radiative recombination.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4d, the PL quenching of the perovskite film grown on MEA‐modified m‐TiO 2 is much more efficient than that of the unmodified m‐TiO 2 , suggesting enhanced electron extraction and reduced charge recombination. [ 27 ] In addition, TRPL spectra collected at the emission peak (760 nm) of the perovskite on bare TiO 2 and MEA‐passivated TiO 2 are shown in Figure 4e. The TRPL spectra showed a biexponential decay, in which the fast decay lifetime ( τ 1 ) can be ascribed to the trap‐assisted nonradiative recombination and the longer decay lifetime ( τ 2 ) can be attributed to the radiative recombination.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Ko et al fabricated a 3D NiO nanowall by a hydrothermal process (Figure 8A). 87 After optimizing the hydrothermal time, the NiO nanowall‐based device exhibited a lower PL intensity, smaller R ct , and higher R rec compared to control nanocrystals film‐based device, suggesting that the NiO nanowall had better charge transport ability (Figure 8B,C). Besides, the hole trap density of NiO decreased from 7.48 × 10 15 cm −3 (nanocrystals film) to 4.51 × 10 15 cm −3 (nanowall array), which directly indicated that the nanowall structured NiO was more effective to passivate the trap states density at the NiO/perovskite interface.…”
Section: Ordered Array Structures For Htlmentioning
confidence: 99%
“…(A) The SEM image of the NiO nanowall at a growth time of 6 h. (B) The PL spectra and (C) EIS measurement of perovskite films on different NiO nanowall. Source: Reproduced from Reference 87 by permission from Wiley‐VCH. (D) Schematic diagram of glancing angle deposition of a NiO x compact layer.…”
Section: Ordered Array Structures For Perovskite Layermentioning
confidence: 99%
“…6,[51][52][53][54][55] Besides, nickel oxide can be synthesized via several methods, including the chemical deposition method, 56,57 solution growth technique, 58 SILAR method, 59 thermal decomposition, combustion method, 60 sonochemical, electrolysis, 61 solid-state reaction, 62 chemical precipitation and chemical combustion methods, 51 pulsed laser deposition 52 amongst others. 53,54 Before delving into the details of our present review, it is important to mention several interesting works on NiO, which relates to its application as HTM. Xu et al reviewed inverted PSCs incorporated with doped NiO as the hole transport layer.…”
Section: Novelty Statementmentioning
confidence: 99%
“…So far, literature on nickel oxide as hole transport material reported a good and stable film with high efficiency 1,34,49,50 . Interests in NiO and NiO‐based devices could be traced to several other advantages including its reduced power usage, memory effect, high energy storage abilities, flexibility, relatively cheap and increased color efficiency when no current flows through 6,51‐55 . Besides, nickel oxide can be synthesized via several methods, including the chemical deposition method, 56,57 solution growth technique, 58 SILAR method, 59 thermal decomposition, combustion method, 60 sonochemical, electrolysis, 61 solid‐state reaction, 62 chemical precipitation and chemical combustion methods, 51 pulsed laser deposition 52 amongst others 53,54 …”
Section: Introductionmentioning
confidence: 99%